2002
DOI: 10.1038/nature01142
|View full text |Cite
|
Sign up to set email alerts
|

A stellar relic from the early Milky Way

Abstract: The chemical composition of the most metal-deficient stars reflects the composition of the gas from which they formed. These old stars provide crucial clues to the star formation history and the synthesis of chemical elements in the early Universe. They are the local relics of epochs otherwise observable only at very high redshifts 1,2 ; if totally metal-free ("population III") stars could be found, this would allow the direct study of the pristine gas from the Big Bang. Earlier searches for such stars found n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
536
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 515 publications
(559 citation statements)
references
References 19 publications
19
536
1
3
Order By: Relevance
“…The mass fraction, Z, of elements more massive than helium, is called "metallicity". A number of very metal poor stars have been found 2,3 , some of which, while having a low iron abundance, are rich in carbon, nitrogen and oxygen 4,5,6 . For theoretical reasons 7,8 and because of an observed absence of stars with metallicities lower than Z=1.5×10 5 , it has been suggested that low mass stars (M‹0.8M ⊙ , the ones that survive to the present day) cannot form until the interstellar medium has been enriched above a critical value, estimated to lie in the range 1.5×10 8 ≤Z≤1.5×10 6[8] , although competing * Gliese Fellow…”
mentioning
confidence: 99%
“…The mass fraction, Z, of elements more massive than helium, is called "metallicity". A number of very metal poor stars have been found 2,3 , some of which, while having a low iron abundance, are rich in carbon, nitrogen and oxygen 4,5,6 . For theoretical reasons 7,8 and because of an observed absence of stars with metallicities lower than Z=1.5×10 5 , it has been suggested that low mass stars (M‹0.8M ⊙ , the ones that survive to the present day) cannot form until the interstellar medium has been enriched above a critical value, estimated to lie in the range 1.5×10 8 ≤Z≤1.5×10 6[8] , although competing * Gliese Fellow…”
mentioning
confidence: 99%
“…Until recently only one star was known to have an iron abundance with [Fe/H] < −4.0 (HE 0107−5240 with [Fe/H] = −5.2; Christlieb et al 2002). Now, a second star, HE 1327−2326, has been found with [Fe/H] = −5.4 (Frebel et al 2005, Aoki et al in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…However, with the latest generation of telescopes and with space based telescopes, such as the Hubble Space Telescope (HST), a much larger range of n-capture elements can be examined. The most metal-poor stars observed to date, HE0107-5240 (Christlieb et al 2002) and HE1327-2326 (Frebel et al 2005), with metallicities below [Fe/H]< −5 are enriched in C, N, and O but very poor in n-capture elements. However, the detection of Sr/Fe (exceeding 10 times the solar ratio) in the most metal-poor star (HE1327-2326, Frebel et al 2005) suggests the existence of a primary process producing elements beyond Fe and Zn.…”
Section: Evidence For a Lighter Element Primary Process (Lepp)mentioning
confidence: 99%